2018
DOI: 10.3389/fneur.2018.00948
|View full text |Cite
|
Sign up to set email alerts
|

Macroscale White Matter Alterations Due to Traumatic Cerebral Microhemorrhages Are Revealed by Diffusion Tensor Imaging

Abstract: With the advent of susceptibility-weighted imaging (SWI), the ability to identify cerebral microbleeds (CMBs) associated with mild traumatic brain injury (mTBI) has become increasingly commonplace. Nevertheless, the clinical significance of post-traumatic CMBs remains controversial partly because it is unclear whether mTBI-related CMBs entail brain circuitry disruptions which, although structurally subtle, are functionally significant. This study combines magnetic resonance and diffusion tensor imaging (MRI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…The occurrence of CMBs in geriatric mTBI patients is relevant to the spatial profile and severity of post-traumatic WM alterations [16, 46, 32]. Previously, we showed that the trajectories and integrities of WM fasciculi passing through the vicinity (penumbrae) of post-traumatic CMBs can be altered in ways which persist for at least six months post-injury [47, 48]. Furthermore, other studies have found that CMB count is associated with network alterations in patients with early AD as well [49].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of CMBs in geriatric mTBI patients is relevant to the spatial profile and severity of post-traumatic WM alterations [16, 46, 32]. Previously, we showed that the trajectories and integrities of WM fasciculi passing through the vicinity (penumbrae) of post-traumatic CMBs can be altered in ways which persist for at least six months post-injury [47, 48]. Furthermore, other studies have found that CMB count is associated with network alterations in patients with early AD as well [49].…”
Section: Discussionmentioning
confidence: 99%
“…All data processing steps are based upon protocols used in past studies conducted in our laboratory [2][3][4][5][6][7].…”
Section: Neuroimage Data Processingmentioning
confidence: 99%
“…After parcellation, the most representative WM streamline in each cluster was identified using a streamline prototyping approach, as described elsewhere [4,5,7]. Briefly, this method can be applied to each WM cluster to facilitate the identification of a unique WM streamline whose trajectory and other properties are representative of the group of streamlines in the cluster.…”
Section: E Wm Parcellation and Prototypingmentioning
confidence: 99%
“…Formally, for each WM streamline prototype, the null hypothesis was formulated as the statement that there is no statistically significant correlation between (A) the longitudinal difference in FA measured at vertices along the prototype streamline and (B) the topological (along-tract) distance between the closest CMB and each vertex along the streamline prototype. The topological distance was selected over the Euclidean distance because the diffusion of neurotoxins away from the CMB site is thought to be constrained by WM axon trajectories [7]. This suggests that the topological (along-tract) distance is a measure which reflects the parameters of the biophysics problem more realistically.…”
Section: F Statistical Analysismentioning
confidence: 99%